Perfil de ácidos graxos no longissimus dorsi de ovinos Santa Inês em crescimento alimentados com diferentes níveis de energia - Arruda, Paulo Cesar Lopes de (2010)
This study evaluated the influence of rations with different levels of metabolizable energy on the content of total lipids, cholesterol and fatty acid profile of the longissimus dorsi of Santa Ines lambs. Twenty Santa Ines lambs were used, with age and body weight of 50 days and 13.0 kg ± 0.56 kg, respectively, fed rations with different energy levels: 2.08; 2.28; 2.47 e 2.69 Mcal/kgDM. The rations influenced the content of total lipids, cholesterol and fatty acid profile of cis 10 -, heptadecanoic and eicosanotrienoic (P<0.05). The relations polyunsaturated fatty acids (PUFA): saturated fatty acids (SFA); PUFA: monounsaturated fatty acids (MUA), MUA: SFA, desirable fatty acids, -6: -3, atherogenicity index, thrombogenicity index, relation between hypocholesterolemic and hypercholesterolemic fatty acids and the relation (C18:0+C18:1):C16:0 were not affected by energy levels (P> 0.05). The dietary manipulation influences the lipid profile in longissimus dorsi of Santa Ines lambs.